2014
DOI: 10.1002/cyto.b.21183
|View full text |Cite
|
Sign up to set email alerts
|

Fine-needle aspiration is superior to needle core biopsy as a sample acquisition method for flow cytometric analysis in suspected hematologic neoplasms

Abstract: Conclusions: FNA was found to be significantly superior to NCB in obtaining material for FCI. However, NCB resulted in fewer indeterminate final diagnoses due to benefit of histologic correlation. In our opinion, NCB for histology combined with dedicated FNA material for FCI may yield the best results for a minimally invasive approach to the diagnosis of hematologic neoplasms. V C 2014 International Clinical Cytometry Society

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 9 publications
(23 reference statements)
0
19
0
Order By: Relevance
“…Comparing to excisional biopsy, core needle biopsy is easy to perform, less traumatic, and does not require general anesthesia. However, the limited biopsy material and poor recovery of cells from core needle biopsies make it difficult triaging specimens for flow cytometry testing . Chi et al reported their experience in using “rinsing” technique of the core biopsy specimens with RPMI media .…”
Section: Flow Cytometry Studies On Hematolymphoid Neoplasmsmentioning
confidence: 99%
“…Comparing to excisional biopsy, core needle biopsy is easy to perform, less traumatic, and does not require general anesthesia. However, the limited biopsy material and poor recovery of cells from core needle biopsies make it difficult triaging specimens for flow cytometry testing . Chi et al reported their experience in using “rinsing” technique of the core biopsy specimens with RPMI media .…”
Section: Flow Cytometry Studies On Hematolymphoid Neoplasmsmentioning
confidence: 99%
“…29 Although excisional lymph node biopsy is the preferred method for the workup of lymphoma, the combination of both FNA and CNB may serve as the best option when a less invasive sampling is required; FNA obtains better material for flow cytometry whereas CNB preserves tissue architecture for histologic correlation. 30…”
Section: Salivary Gland Lesionsmentioning
confidence: 99%
“…In a large meta‐analysis of CNB and FNA for the subclassification of lymphoma, the median rate of nonactionable diagnoses for CNB was approximately 15%, whereas the nonactionable diagnostic rate was approximately 25% for FNA . Although excisional lymph node biopsy is the preferred method for the workup of lymphoma, the combination of both FNA and CNB may serve as the best option when a less invasive sampling is required; FNA obtains better material for flow cytometry whereas CNB preserves tissue architecture for histologic correlation …”
Section: Introductionmentioning
confidence: 99%
“…Finally, in this issue, there are two articles reporting technical innovations for the clinical laboratory. This journal is an excellent forum to share experiences with various techniques associated with clinical flow cytometry, and it is hoped that the readership will benefit from the current submissions (21,22) as well as recently published technical reports (23,24). Vallangeon and coworkers (21) studied the effects of tissue disaggregation methods on the immunophenotypic detection of diffuse large B cell lymphomas.…”
Section: Technical Innovations For the Clinical Labmentioning
confidence: 99%